Pemberantasan Penyalahgunaan dan Peredaran Narkotika Melalui Pararem Desa Adat Pancasari - Kadek Andy krisnanta; I Made Suwitra; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2020)
The increase in the spread of narcotics in Indonesia is influenced by the rapid population growth. Bali is one of the global tourist destinations and has become a spot for the spread of narcotics and other dangerous substances. The eradication of narcotics in the area in turn requires the synergy of various components in order to suppress and limit the space for dealers both small and large scale. The collaborative effort to eradicate the distribution and abuse of narcotics is carried out by BNNK Buleleng by cooperating with traditional villages through the issuance of a pararem concerning Narcotics in Desa Pancasari, the Sub-district of Buleleng. This research makes use of empirical legal methods. Data were analysed qualitatively, descriptively and systematically. The collaboration between BNNK Buleleng and the Desa Adat of Pancasari in the form of Pararem Number 01/DPP-II/2019 concerning Narcotics is used as a tool to eradicate the existence of narcotics with the aim to limit the space for spread starting from the smallest scope of society. Then, in terms of effectiveness, the Pararem Number 01/DPP-11/2019 in the eradication of narcotics abuse and circulation in the Desa Adat of Pancasari has been effective with the full support of the village government and indigenous peoples as well as the role of the BNNK Buleleng as a supervisor that until now there has been no violation of the Pararem in the indigenous villages of Pancasari.